Penerapan Pendekatan TaRL pada Mata Pelajaran Matematika Kelas 1 di SDN Gayamsari 02 Semarang Semarang - Evi Nur Izzati; Mei Fita Asri Untari; Espiyati Espiyati (Journal on Education, 2024)
This research aims to describe the application of the TaRL approach in Grade 1 Mathematics Subjects at SDN Gayamsari 02 Semarang. The background to this research is one of the implementations of differentiated learning, that is, it is known that the characteristics and learning styles of students are different, so learning is needed that suits the needs of each student. The method used in this research is descriptive qualitative. This research is aimed at describing differentiated learning using the TaRL (Teaching at The Right Level) approach. The subjects of the research carried out were all students in class 1a of SDN Gayamsari 02 Semarang. The research results show that the Teaching at the Right Level (TaRL) approach uses a cooperative learning model and learning media "mystery box", power points, and learning videos that can be used by all students who have three different learning styles.